Lewis Acid Ionic Liquid Immobilized on Chitosan for Synthesis of Dichlorophenylphosphine - Qiu, Xian-Hua; Xie, Yu; Wang, Xiao-Ying; Cao, Qian-Yong; Tang, Xing-Hua; Hu, Jin-Gang; Hong, Xiao-Wei; Yan, Si-Feng (Asian Journal of Chemistry, 2012)
Lewis acid ionic liquid immobilized on chitosan as a new catalyst was prepared via the synthesis of l-trimethoxy-silylpropyl-3-methylindazoliumchloride-AlCl3, l-trimethoxy-silylpropyl-3-methylindazolium-chloride-InCl3 and l-trimethoxy-silylpropyl-3-methylindazolium-chloride-FeCl3 and then grafting them to chitosan respectively. Their catalytic activities were investigated in the synthesis of dichlorophenylphosphine. The results showed when the three catalysts' amounts were 0.0225, 0.0195 and 0.015 g respectively, the substrate of benzene could be completely transformed into dichlorophenylphosphine on the conditions of the phosphorus trichloride 0.22 g, the molar ratio of phosphorus trichloride to benzene 1.8 : l, the reaction temperature 75 ºC and the reaction time 120 min. Moreover, the molar ratios of ionic liquid moiety to benzene were merely 0.285, 0.187 and 0.172 % respectively, which were much lower than that of the corresponding pure ionic liquids to benzene. The catalyst can be reused for many times with fine catalytic efficiency. In addition, the new catalyst using chitosan with the higher deacetylation degree as carrier could improve catalytic activity and reusability.